Evaluation of Teaching Patterns at Kusala Citta Buddhist Sunday School, North Lombok Regency - Ade Supandi Nata Kusuma (STAB Kertarajasa, 2022)
The purpose of this research is to identify and assess teaching patterns at the Kusala Citta Buddhist Sunday School. This style of investigation is qualitative with descriptive analysis. This study's data gathering methods included observation, interviews, and documentation. Five teachers of the Kusala Citta Buddhist Sunday School and three representatives of Kusala Citta Buddhist Sunday School students provided the data for this research. The findings of this research indicate that students are inactive participants in the learning process due to the low implementation of instructional patterns. At Kusala Citta Buddhist Sunday School, the traditional teaching pattern and the technological teaching pattern are often used as instructional strategies. In conducting the examination of teaching patterns at Kusala Citta Buddhist Sunday School, the significance of curricular guidance in the implementation of learning was determined. The curriculum is the teacher's primary instructional base. Before teaching, the teacher must create a Learning Implementation Plan to make it simpler for them to establish patterns, approaches, and strategies. Students become learning centers throughout the learning process so they may explore their potential, perfect their abilities, and communicate their views. In order to inspire Buddhist Sunday School students to think critically and prudently, teachers must be able to create an engaging learning environment. In developing instructional patterns, techniques, and strategies, teachers must be creative and imaginative.